Emerging nailfold capillaroscopic patterns in COVID-19: from acute patients to survivors - M. Cutolo; A. Sulli; V. Smith; E. Gotelli (PAGEPress Publications, 2023)
The SARS-CoV-2 infection causing the Coronavirus disease-19 (COVID-19) is characterized by a broad range of clinical manifestations, implicating microvascular damage with endothelial dysfunction and different organ involvement.